COMPARATIVE EVALUATION OF MORPHOMETRIC TRAITS AND THEIR ASSOCIATION WITH SEX AND BODY WEIGHT IN THREE INDIGENOUS CHICKEN ECOTYPES OF NORTH-CENTRAL NIGERIA - Sani, Umar M.; Dogara, Umar M.; Mundi, Harirat H.; Abdullahi, Hudu R.; Abdullahi, Zainab; Mundi, Ismaila (FUDMA Journal of Sciences, 2026)
The future improvement of indigenous chicken production systems largely depends on the availability and effective utilization of their genetic variability. The relationship between body weight and morphometric traits is important in planning breeding. Therefore, this study evaluated morphometric traits and their relationships with body weight and sex in three indigenous chicken ecotypes from Nasarawa, Benue, and Plateau States, Nigeria. A total of 120 mature chickens, comprising 40 birds each from the Fulani, Kwalla, and Tiv ecotypes aged 18–24 weeks, were used. The birds were managed under a semi-intensive system. Body weight was measured weekly using a weighing balance. Linear body measurements including breast girth, body length, shank length, wing length, and keel length were obtained using a measuring tape (cm), while comb length, wattle length, beak length, comb height, spur thickness, wattle width and height, and ocular dimensions were measured using a digital vernier caliper. Data were subjected to analysis of variance and correlation analyses. Significant (P < 0.05) differences in body weight were observed among the ecotypes. The Kwalla ecotype had the highest mean body weight (1.50 kg), followed by the Tiv (1.38 kg) and Fulani (1.25 kg) ecotypes. Sex had a highly significant effect (P < 0.05) on body weight. Several morphometric traits, including beak length, comb height, wattle length, ocular length, and spur thickness, differed significantly (P < 0.05) across ecotypes and sexes.